2023
DOI: 10.3390/mi14091664
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Characterisation of TiO2-rGO Field-Effect Transistor as a Platform for Biosensing Applications

Anis Amirah Alim,
Roharsyafinaz Roslan,
Sh. Nadzirah
et al.

Abstract: The performance of the graphene-based field-effect transistor (FET) as a biosensor is based on the output drain current (Id). In this work, the signal-to-noise ratio (SNR) was investigated to obtain a high-performance device that produces a higher Id value. Using the finite element method, a novel top-gate FET was developed in a three-dimensional (3D) simulation model with the titanium dioxide-reduced graphene oxide (TiO2-rGO) nanocomposite as the transducer material, which acts as a platform for biosensing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Previous studies prove that the most suitable output current for biosensor applications is in the range of microns and nanoamperes [28]. The simulation study in previous work has shown that the TiO2/rGO material increases its current performance by reducing the gap of the channel [21]. In this study, we have proved experimentally that TiO2 and TiO2/rGO could conduct in smaller channel lengths with current output in the range of microns.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies prove that the most suitable output current for biosensor applications is in the range of microns and nanoamperes [28]. The simulation study in previous work has shown that the TiO2/rGO material increases its current performance by reducing the gap of the channel [21]. In this study, we have proved experimentally that TiO2 and TiO2/rGO could conduct in smaller channel lengths with current output in the range of microns.…”
Section: Resultssupporting
confidence: 55%
“…The transducer material in the channel region acts as a connection, converting the external charge of biomolecule interaction. Previous work [21], has explained further information on the theoretical algorithm.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In accordance with an orthogonal array L 18 (2 1 × 3 7 ) revised by engineers [ 24 ], the experimental setup involved the utilization of 0.55 mm polypropylene extruded sheets for molding production experiments. Following the original design parameters, experiments were conducted at L Factory, and the products were subjected to inspection and quantification.…”
Section: Research Methods and Analysis Experimentsmentioning
confidence: 99%